2004
DOI: 10.1007/s00134-003-2047-x
|View full text |Cite
|
Sign up to set email alerts
|

Citrate vs. heparin for anticoagulation in continuous venovenous hemofiltration: a prospective randomized study

Abstract: Regional citrate anticoagulation seems superior to heparin for the filter lifetime and transfusion requirements in ICU patients treated by continuous renal replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
242
5
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(278 citation statements)
references
References 16 publications
23
242
5
8
Order By: Relevance
“…Although the use of standard sodium concentration CRRT solutions has also been reported in RCA protocols adopting hypertonic citrate formulations (68,69), these solutions are usually combined with customized low-sodium dialysis/replacement fluids to prevent hypernatremia. As long as a well designed protocol is implemented, hypertonic citrate solutions can be used to perform RCA with all modalities of CRRT ( Figure 2, Table 1) (15,16,18,46,47,49). RCA protocols based on hypertonic citrate solutions use citrate as the primary buffer, regardless of CRRT modality.…”
Section: High-concentration Citrate Solutions (Hypertonic In Sodium)mentioning
confidence: 99%
See 3 more Smart Citations
“…Although the use of standard sodium concentration CRRT solutions has also been reported in RCA protocols adopting hypertonic citrate formulations (68,69), these solutions are usually combined with customized low-sodium dialysis/replacement fluids to prevent hypernatremia. As long as a well designed protocol is implemented, hypertonic citrate solutions can be used to perform RCA with all modalities of CRRT ( Figure 2, Table 1) (15,16,18,46,47,49). RCA protocols based on hypertonic citrate solutions use citrate as the primary buffer, regardless of CRRT modality.…”
Section: High-concentration Citrate Solutions (Hypertonic In Sodium)mentioning
confidence: 99%
“…Several studies comparing citrate-based protocols with heparin-based protocols have reported better filter survival and/or fewer bleeding events during RCA (14)(15)(16)(17)(18)(19). Two separate meta-analyses, including six randomized trials comparing RCA with systemic anticoagulation with heparin, confirmed a significant decrease of bleeding events in the citrate arm (70,71); however, they provided slightly different results about filter survival.…”
Section: Safety and Efficacy Of Rcamentioning
confidence: 99%
See 2 more Smart Citations
“…Citrate regional anticoagulation has gained significant popularity over the previous decade and is used exclusively in some centers for CRRT. [134][135][136] Two studies document the safety of citrate, avoiding anticoagulation and bleeding, with improved circuit survival compared to heparin in adults. 135,136 Citrate is delivered pre-filter as tri-sodium citrate, which chelates calcium in the circuit with the goal of 0.4 mmol/l ionized calcium at the filter, and calcium is re-infused to the patient to prevent systemic hypocalcaemia.…”
mentioning
confidence: 99%